1989
DOI: 10.1007/bf00005968
|View full text |Cite
|
Sign up to set email alerts
|

Erosion, phosphorus and phytoplankton response in rivers of South-Eastern Norway

Abstract: The development of P fractions and phytoplankton was studied in three rivers with varying concentrations of seston.Less than 1% of the yearly TP transport may take place during periods with high algal biomass. The observation of a high growth rate of phytoplankton in the rivers coinciding with high concentrations of RP, low content of seston and high TP:Chl a ratio, indicate that the growth was often not P-limiting. During short periods with high phytoplankton biomass the ratio TP:Chl a may be low, indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Furthermore, not only the dissolved P contributes to eutrophication, since when the stream water enters a lake, the particulate P (PP) in the SS of the stream water begins to re-equilibrate with the standing water's dissolved P (Correll, 1998). Hence, much of the PP inputs become available to the phytoplankton and bacteria (Krogstad and Løvstad, 1989;Ekholm, 1994;Reynolds and Davies, 2001). Haraldsen et al (1995) described the regional differences in P loss processes and concluded that erosion and related losses of PP were the most important process of P loss on arable land in south-eastern Norway, while losses of dissolved P related to manure application and point sources were more important in the south-western part of the country where livestock density is generally high.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, not only the dissolved P contributes to eutrophication, since when the stream water enters a lake, the particulate P (PP) in the SS of the stream water begins to re-equilibrate with the standing water's dissolved P (Correll, 1998). Hence, much of the PP inputs become available to the phytoplankton and bacteria (Krogstad and Løvstad, 1989;Ekholm, 1994;Reynolds and Davies, 2001). Haraldsen et al (1995) described the regional differences in P loss processes and concluded that erosion and related losses of PP were the most important process of P loss on arable land in south-eastern Norway, while losses of dissolved P related to manure application and point sources were more important in the south-western part of the country where livestock density is generally high.…”
Section: Introductionmentioning
confidence: 99%
“…Surface water quality is also affected by variations in hydro-climatic conditions (Durance and Ormerod, 2010) and nutrient availability is not the only limiting factor of phytoplanktonic growth in rivers: successful phytoplankton species in rivers are selected based on their ability to survive high-frequency irradiance fluctuations and the important determinants are turbidity (or its impact upon underwater light) and water residence time (Istvánovics and Honti, 2012;Krogstad and Lovstad, 1989;Reynolds and Descy, 1996;Reynolds et al, 1994). In Europe, both climatic models and observations have shown a general rise in air and water temperature since the 1970s (Moatar and Gailhard, 2006;Whitehead et al, 2009;Bustillo et al, 2013), and models predict lower water discharge and rising temperatures during summer, potentially intensifying the risk of eutrophication (Arheimer et al, 2005;Barlocher et al, 2008;Lecerf et al, 2007;Whitehead et al, 2009) as shallow rivers are particularly susceptible (Istvánovics et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…, 2004). The influence of factors like residence time on phytoplankton dynamics can be particularly pronounced in lotic ecosystems because of large shifts in flow rates related to changes in rainfall in the catchment (Jones, 1984; Soballe & Kimmel, 1987; Reynolds, 1988; Krogstad & Lovstad, 1989; Pace, Findlay & Lints, 1992). While Basu & Pick (1996) highlight the importance of nutrient availability in defining phytoplankton biomass potential in rivers, the achievement of that potential can be strongly influenced by other considerations, such as water residence time, light availability and grazing loses.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have stressed the importance of water residence time in defining the relationships between nutrient status and phytoplankton standing crops in rivers (Vannote et al. , 1980; Jones, 1984; Soballe & Kimmel, 1987; Reynolds, 1988; Krogstad & Lovstad, 1989; Pace et al. , 1992).…”
Section: Introductionmentioning
confidence: 99%